Modern pharmacological treatment of obese patients. (January 2020) - May, Marcus; Schindler, Christoph; Engeli, Stefan
There are many angles to consider in drug treatment of obese patients. On the one hand, some specific weight loss drugs are available, on the other, several drugs are associated with unintentional weight changes. When treating an obese patient for any given disease, several physiological changes may influence the pharmacokinetic properties of the drugs required. Thus, increased body weight may influence the efficacy and safety of some drug treatments. Even more complicated is the situation after weight reduction surgery. Due to the various changes to the gastrointestinal tract induced by the different surgical techniques used, and the dynamic changes in body composition thereafter, drug dosing has to be constantly reconsidered. Whereas all of these issues are of clinical importance, none of them have been investigated in the necessary depth and broadness to ensure safe and efficacious drug treatment of the massively obese patient. Individual considerations have to be based on comorbidities, concomitant medication, and on specific drug properties, for example, lipophilicity, volume of distribution, and metabolism. In this article we summarize the data available on different aspects of drug treatment in the obese patient with the hope of improving patient care.